Ganged Up On: How the US immigration system penalises and fails to protect Central American minors who are trafficked for criminal activity by gangs - Soltis, Katherine; Taylor Diaz, Madeline (Anti-Trafficking Review, 2021)
This article addresses the failures of the United States immigration system to protect Central American minors who were trafficked for exploitation in criminal activities by gangs. In particular, it focuses on the ways in which the US immigration system denies humanitarian protection to Central American minors who were forced to participate in criminal activity by the Mara Salvatrucha (MS-13) and 18th Street gangs, and instead detains them. The article will examine this trend in the context of a larger proclivity to criminalise immigration in the US, particularly minors fleeing violence in Central America. We draw upon our experience representing Central American minors in their applications for humanitarian immigration relief to highlight how the US immigration system fails to protect this vulnerable population and penalises these children for their own victimisation.